Single-site treatment of cystic intestinal duplication malformations via the umbilicus - Xia, Tian; Qin, Hong; Tang, BingQiang (Frontiers in Surgery, 2025)
ObjectiveTo summarize the diagnosis and treatment experience of small intestinal duplication malformations in our hospital.MethodsWe retrospectively analyzed data from 90 children undergoing surgery for intestinal duplication malformations at our hospital from October 2019 to October 2024. All patients underwent transumbilical single-site laparoscopic-assisted resection. A 1.5 cm longitudinal umbilical incision was made, followed by layered dissection of the skin and subcutaneous tissue. Two 5 mm trocars were placed at the incision edges to establish CO2 pneumoperitoneum. Bowel graspers were inserted to locate lesions under direct vision. First, the abdominal cavity was examined. The intestinal tube was initially checked for any mass, adhesion, or obvious congestion and edema. This is mostly where the lesion is located. If it is not found, retrograde exploration of the small intestine begins from the ileocecal area. After identifying the mass, it was fixed with absorbable sutures. The trocars and laparoscope were removed, the fascia and peritoneum were incised, and the mass with attached bowel was exteriorized through the umbilical incision. Based on lesion characteristics, enucleation of the duplication cyst or bowel resection with anastomosis was performed. Specimens were sent for pathology.ResultsAll surgeries succeeded (duration: 45–95 min). Oral intake resumed within 1–4 days, and discharge occurred at 5–14 days postoperatively. Enucleation was performed in 74 cases, while bowel resection with anastomosis was required in 16 cases (including 5 terminal ileal resections with anastomosis 1.5–2 cm from the ileocecal valve). No complications (incisional infection, anastomotic leakage, stenosis, adhesive bowel obstruction, or incisional hernia) occurred. Pathology confirmed intestinal duplication malformations.ConclusionIntestinal duplication malformations predominantly affect the terminal ileum. Enucleation is optimal, but resection-anastomosis is safe when enucleation is difficult, avoiding enterostomy and reducing patient discomfort. Single-site laparoscopy offers minimal invasiveness and excellent cosmetic outcomes.